Pendampingan Pendaftaran Merek Bagi Usaha Mikro Kecil dan Menengah Berbasis Masyarakat Desa - Triyana, Lily; Subroto, Aryo; Susansi, Sri; Susmiyati, Haris Retno; Al Hidayah, Rahmawati; Harjanti, Wiwik; Alfian (FLEKSIBEL: Jurnal Pengabdian Masyarakat, 2022)
Micro, Small and Medium Enterprises (UMKM) activities are an alternative to increase community economic growth, including rural communities. However, with the large potential of UMKM, there are problems that can weaken the rights of UMKM, one of which is trademark registration for products produced by UMKM activities. This condition also occurs in UMKM actors in Separi Village, Tenggarong Seberang District. Therefore, it is necessary to conduct socialization to increase legal understanding for the public on the urgency of trademark registration and assistance to UMKM actors in the process of registering their marks. The method used in this activity is counseling and mentoring which is carried out through three stages, namely mapping the potential of UMKM, delivering law informations, and assisting in trademark registration. The result is an increase in legal understanding for the community and UMKM actors regarding trademark registration, as well as the registration of product brands from 1 (one) UMKM actor in Separi Village. This shows that it is important to carry out an empowerment process by increasing the legal understanding capacity of the community